2018
DOI: 10.3390/su10020402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Erratic Rainfall from Climate Change on Pulse Production Efficiency in Lower Myanmar

Abstract: Erratic rainfall has a detrimental impact on crop productivity but rainfall during the specific growth stage is rarely used in efficiency analysis. This study focuses on this untapped point and examines the influence of rainfall specifically encountered during the sowing stage and early vegetative growth stage and the flowering stage of pulses on productivity and efficiency in Lower Myanmar using data from 182 sample farmers. The results of a stochastic frontier production function reveal that rainfall inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 22 publications
(38 reference statements)
2
34
0
1
Order By: Relevance
“…A TE score closer to 1 implies that a coffee producer is producing nearer to the maximum output feasible level. Jondrow et al [24] suggested that the level of TE can be predicted using the conditional expectation of u i , given the disturbance term ε i , which is defined in Equation 4as follows [25,26]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A TE score closer to 1 implies that a coffee producer is producing nearer to the maximum output feasible level. Jondrow et al [24] suggested that the level of TE can be predicted using the conditional expectation of u i , given the disturbance term ε i , which is defined in Equation 4as follows [25,26]:…”
Section: Methodsmentioning
confidence: 99%
“…For this study, the likelihood ratio test indicates that CD production function is the most appropriate functional form that effectively fits our data than the TL. The model is then specified as follows [21,25,27]:…”
Section: Methodsmentioning
confidence: 99%
“…Technical efficiency can be analyzed by using parametric or non-parametric methods. Both methods have their strengths and weaknesses [62][63][64][65]. Given the wide scope of factors of production considered and the relatively small sample size, regression analysis using the translog production function may have low efficiency and high uncertainty.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…The time-varying risk characteristics of grain YPUA and the impact on the premium rate have been ignored. The risk of grain YPUA may have obvious time-varying characteristics due to the improvement in agricultural disaster prevention capability, the progress of agricultural technology, the adjustment of the agricultural industrial structure, and changes in a disaster situation [26,27]. Generally, crop YPUA risk is a random or proportional volatility with time or yield growth, corresponding to the constant variance or proportional variance in the yield trend estimation.…”
Section: Pure Premium Ratemaking Based On Time-varying Risk Adjustmentmentioning
confidence: 99%